Students’ Preferences Toward Virtual, Classroom, and Blended Learning - Wiguna, I Gusti Ngurah Wira (Journal of Educational Study, 2022)
This research aims to find out the learning system that students want after the COVID-19 pandemic, and the reason they chose the learning system. This study uses various survey methods. The subject of this study was all 11th grade students at SMA Negeri 2 Negara. This study uses google form questionnaires as research instruments. The research instrument consists of 11 indicators divided into 48 statements. The data obtained from the questionnaire are the student's response, which then the number of responses is summed and divided to find the average score of the student's response for each learning system. Scores from each learning system (virtual/online, classroom/face-to-face, and blended) are compared. The results of the study showed that students in SMA Negeri 2 Negara prefer to learn with a face-to-face learning system compared to blended learning systems and online / virtual learning systems. The reason students in SMA Negeri 2 Negara prefer face to face learning is because they can understand the material better through direct interaction with teachers and students.